Analysis of Seaweed Cracker Product Marketing Strategy at the Marine and Fisheries Independent Training Center (P2MKP) Balikpapan City, East Kalimantan - Suwardi Gunawan; Willy Tambunan; Ahmad Subarkah (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2019)
Pusat Pelatihan Mandiri Kelautan dan Perikanan (P2MKP) is a seaweed cultivation business field that located in Jalan Mulawarman Gang Anyer RT.13 No. 44 Manggar, Balikpapan City, East Kalimantan. The selling method they applied has no specific strategy in marketing, the selling method they applied only provide current needs of customers.Strategy formulation starts with the input stage to formulating the strategy; identify and analyze the factors of internal and external company’s environment. The next stage is the matching stage to result a proper strategy alternative with combining the internal and external factors. The result of IFE and EFE matrix included into IE matrix to detect company location. After the location of company was detected in the IE matrix, then SWOT analysis was required to formulate strategy alternative. The last stage, decision stage, it decides which one will be the priority with using Analysis Hierarchy Process as recommended strategy for the company. It results strategy is;(1) Maintain a relationship with the government to get patent product license, (2) To create an innovation of products with using technology and occur coordination with related instances to get BPOM RI and halal certification, (3) To maintain a cooperation to get government support in widening the marketing area, (4) Increasing production or stocks volume with using technology, (5) To reach the efficient production cost with maintaining the same product price, and the sixth strategy is build the partnerships to increasing the quality of product so the customer value is achieved.